Gibberellic acid and cluster thinning on seedless grape 'BRS Clara' in caxias do sul, rio grande do sul state, Brazil - Formolo R.* (2010)
This study presents the effects of different concentrations of gibberellic acid and cluster thinning in seedless grape 'BRS Clara'. The experiment was conducted in Caxias do Sul city, Rio Grande do Sul State, Brazil. The plants were spaced by 2.4×1.5 m, cultivated under plastic cover and the training system used was double parallel cordon with sloped catch wires. The experimental design was conducted in a randomized block design, with three blocks and one plant per plot. The treatments were T1 - control, without cluster thinning and without application of GA3; T2 - without cluster thinning and single application of 60 mg L-1 of GA3; T3 - without cluster thinning and double application of GA3, 30 mg L-1 + 30 mg L-1, the second application was made 30 days after the first; T4 - cluster thinning, leaving 20 bunches per plant and single application of 60 mg L-1 of GA3; T5 - cluster thinning, leaving 20 bunches/plant and double application of GA3, 30 mg L-1 + 30 mg L-1, the second application was made 30 days after the first. The first application of GA3 was made when the berry was 5 mm in diameter. During the ripening were evaluated the production per plant, cluster weight, cluster length, 50 berries weight, the length and diameter of berries, number of berries per cluster, rachis weight, total soluble solids, acidity, pH and the relation between total soluble solids and acidity (ratio). Double applications of GA3, associated with cluster thinning improved the characteristics of cultivar 'BRS Clara', increasing the berry diameter and cluster weight. The GA3, associated with cluster thinning standardized the average cluster size of 'BRS Clara', ideal condition for packed fruit marketing.